Comparative study between Arabic and Malay - Bahjat, Munjid Mustafa (s.n, 2012)
This research explores a collection of studies that relate to Arabic and Malay languages and theirs literature's. It deals with the exchange of cultures which can connect impact, influence and interaction between the two languages on linguistic and literary levels which can be attained through comprehensive and short studies